1999
DOI: 10.1046/j.1365-3059.1999.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the latent period of the rose powdery mildew pathogen, Sphaerotheca pannosa

Abstract: The effects of temperature on the length of the latent period of rose powdery mildew, caused by Sphaerotheca pannosa var. rosae, were studied. At constant temperatures over the range of 10-28ЊC, the length of the latent period ranged from 4 to 10 days. The relationship between temperature and the rate of fungal development during the latent period (expressed as the reciprocal of the latent period) was described by a nonlinear (thermodynamic) model. The resulting curve was asymmetrically bell-shaped with an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
3
23
0
1
Order By: Relevance
“…This time point is preceded by a 5-6 day latent period, which is in line with 5 days for other genotypes at optimal conditions (Frinking and Verweij, 1989;Xu, 1999) and a 6 day period with mild symptom development. The symptoms increased dramatically after 11 dpi when a second infection cycle became evident.…”
Section: Discussionsupporting
confidence: 71%
“…This time point is preceded by a 5-6 day latent period, which is in line with 5 days for other genotypes at optimal conditions (Frinking and Verweij, 1989;Xu, 1999) and a 6 day period with mild symptom development. The symptoms increased dramatically after 11 dpi when a second infection cycle became evident.…”
Section: Discussionsupporting
confidence: 71%
“…In strawberry leaves inoculated with Colletotrichum acutatum conidia and incubated at different temperatures with continuous wetness, the number of germinated conidia tended to decrease with increasing temperature due to cell lysis [55]. Xu [46] also found that low rate of disease development in rose powdery mildew at supraoptimal temperatures is likely due to higher mortality of spores.…”
Section: Discussionmentioning
confidence: 98%
“…Disease severity in round-leaved mallow inoculated with Colletotrichum gloeosporioides [44] and in soybean infected with Colletotrichum truncatum [45] increased with increase in temperatures between 10 and 25°C and sharply decreased at 30°C. With regard to incubation period, Xu [46] and Xu and Robinson [47] noted that the median incubation period was longer at lower and higher temperatures than at intermediate temperature ranges in rose and hawthorn powdery mildew.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that naturally intact leaves are insufficient for stock cultures of mildew because contamination with other mildew strains often occurs. For Rosaceae belonging to strawberry, the latent infection by Sphaerotheca pannosa 16 and Podosphaera clandestina 17 have been reported on rose and hawthorn, respectively. It is important to use seedlings from sterilized seeds as described in this paper to prevent contamination with other powdery mildew strains.…”
Section: Effects Of Low-temperature Preservation Onmentioning
confidence: 99%